Statina-source localization in solids - David Sajan Mangalam (2012)
Source Localization of Acoustical Signals on solids surfaces is one of the challenges that is being addressed here. The modeling of the presence of noises while measuring the acoustic pressure field produced due to the sound sources in the vicinity is done using acoustical holography method. The pressure field produced is modeled mathematically using RayleighSommerfield Algorithm and Helmholtz integral. Near Field Acoustical Holography (NAH) is performed using the conventional method termed as Fourier Transform based Acoustical Holography. This mathematically modeled pressure field is extrapolated and NAH is performed to reconstruct the original pressure field and localizing the actual acoustical source location on the solid copper plate. A pipeling method is described for extrapolating the truncated pressure field to match the field that was actually measured. Windowing techniques are adopted to address spectral leakage effects and the abnormalities caused close to the boundaries of the copper plate. The stimulation results shows that the method of extrapolation flairs better compared to the zero-padding methodology adopted before NAH. Reconstruction errors are determined to validate the accuracy of the source that is localized on the copper plate.